The Impact of Geopolitical Risk, State Ownership, and Group Affiliations on Indonesian Firms' Cash Reserves - Sandra, Sandra; Kim, Sung Suk (University of Merdeka Malang, 2022)
The purpose of this study is to examine whether geopolitical risks affect firms' cash reserves in Indonesia. Using a panel data analysis, we analyze the role of GPR (short for geopolitical risk) on firms' cash reserves from 2010 to 2020. The results reveal that firms spend their cash reserves when encountering geopolitical risk, specifically financially constrained firms. We extend our study by investigating the effects of state ownership and group affiliations on firms' attitudes towards GPR. State ownership positively affects the relation of GPR and firms' cash reserves, while group affiliation doesn't show a notable impact. The result was robust to endogeneity issues. However, further studies are still needed to determine the extent of geopolitical risk impacts firms' performances. This research is hoped to be useful for policy-makers to anticipate appropriate future regulations in order to help entrepreneurs and the country's economic growth. As for the practitioner itself, i.e., firms, business owners, and entrepreneurs, this research is expected to provide notable information about the impact of risk on firms in Indonesia. Since the economy is shifting to a borderless economy, it can be one of the considerations in making business or economic decisions when firms are faced with geopolitical uncertainty.